Implementation Framework for Merdeka Belajar Kampus Merdeka (MBKM) in Higher Education Academic Activities - Supriati, Ruli; Royani Dewi, Elisa; Triyono; Supriyanti, Dedeh; Azizah, Nur (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
Merdeka Belajar Kampus Merdeka (MBKM) is the policy of the Minister of Education, Culture and Independent Culture aims to encourage students to study various sciences that will help them enter the world of work. The implementation of the MBKM program in extracurricular Education courses must have added value for teachers, students, and education staff. Based on the field survey, this survey leads to a discussion on the level of academic participation in the implementation of MBKM. The purpose of this study is to explain the preparation for implementing the MBKM program and the obstacles. Methods This survey was conducted through a descriptive survey using a survey methodology. The subjects in this study were lecturers, students, and education staff in the PLS research program. Research results from the academic community understand MBKM in the research program environment, the MBKM curriculum document is edited, the research program has courses related to the MBKM program, and entrepreneurial activities support MBKM. The obstacles are limited funds, the academic information system is not optimal, lack of talent, lack of information about the MBKM program.